2005
DOI: 10.1021/ct050132o
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanics/Molecular Mechanics Calculations of the Vanadium Dependent Chloroperoxidase

Abstract: Large quantum mechanics/molecular mechanics (QM/MM) calculations are used to probe the resting and initial protonated states of the vanadium dependent chloroperoxidase from the pathogenic fungus Curvularia inaequalis. QSite was used to model 433 residues and 24 structural waters with molecular mechanics, while 8 active-site residues and the vanadate cofactor (161 atoms) were represented at the B3LYP/lacvp* level of theory. Our previous study of small model systems implied that the resting state of the enzyme c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
58
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 54 publications
12
58
1
Order By: Relevance
“…28 The first step in the catalytic cycle is believed to be protonation of the vanadate, and the QM/MM studies on the native-form of VCPO showed that a configuration containing an axial water and one hydroxo group in the equatorial plane is significantly lower in energy than any other configuration. 26 We have applied a QM/MM scheme to study various …”
Section: Introductionmentioning
confidence: 99%
“…28 The first step in the catalytic cycle is believed to be protonation of the vanadate, and the QM/MM studies on the native-form of VCPO showed that a configuration containing an axial water and one hydroxo group in the equatorial plane is significantly lower in energy than any other configuration. 26 We have applied a QM/MM scheme to study various …”
Section: Introductionmentioning
confidence: 99%
“…In parallel, DFT calculations were carried out on large models of VC1PO active site (145). The above calculations suggest that in the resting state, at least one equatorial oxygen needs to be protonated to stabilize the metal cofactor (123,125,144,145). According to the DFT results, the equatorial hydroxo group is likely to be bound to Ser-402 (145).…”
Section: )mentioning
confidence: 89%
“…Again we emphasize the observation that this active site is also observed for a series of acid phosphatases, indicating consequences of the chemical similarities of vanadate and phosphate (120). Enzymological (121), spectroscopic (122), and both synthetic (57,43) and computational models (48,(123)(124)(125) studies have elucidated key steps in the major catalytic steps in these systems (121). There is no evidence for redox cycling of the vanadate co-factor during catalysis {121, 122).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations